(untitled) (Baghdad Science Journal, 2022)
This study was conducted on Lake Hamrin situated in Diyala governorate, focal Iraq, between latitudes 44º 53ʹ 26.16 ’- 45º 07 ʹ 28.03ʺ and 34º 04ʹ 24.75ʺ ــ 34º 19ʹ 12.74ʺ . As in this study, the surface area of Hamrin Lake was calculated from satellite images during the period from October 2019 to September 2020, with an average satellite image for each month, furthermore,by utilizing the Normalized Differences Water Index (NDWI), the largest surface area was 264,617 km2 for October and the lowest surface area 140.202 km2 for September. The surface temperature of the lake water was also calculated from satellite images of the Landsat 8 satellite, based on bands 10 (Thermal Infrared 1) and 11 (Thermal Infrared 2) that are sensitive to thermal radiation, as the highest surface temperature reached in June 45.49°C degrees Celsius due to the high temperatures for this month and the lowest in February 3.09°C degrees Celsius, which is one of the months in which temperatures drop to the lowest level. The utilization of remote sensing and GIS innovations has helped a lot in checking changes, whether in surface area or temperature, which saves effort, time and cost. The results of this study put decision makers in taking the necessary precautions for the seasons of water scarcity and drought to meet the community’s water needs in the areas of multiple human consumptions and at the same time take advantage of rainy seasons and water abundance to develop long-term strategic plans to maintain a sustainable water balance.